Experimental studies on the wear and mechanical properties of Al7075-B4C-Al2O3 composite. Issue 1 (February 2021) - Balasubramanian, T; Ganesh, M; Subramanian, M; Arunkumar, N; Aswin, S
Abstract: In order to deal with the demands of current requirements, traditional metals require changes in some properties. The high strength and light weight application of aluminium is well known. In certain instances, its ductility prevents its application in some environments. In the existing research, Al 7075 is reinforced with materials such as boron carbide (B4 C) and aluminum oxide (Al2 O3 ) to achieve low mass, low weight, high power, superior malleability, easy machining and excellent corrosion resistance. Thus, hybrid MMC production is being carried out to enhance these mechanical properties. In this study, Al 7075 is cut into small pieces with 90% wt in the form of a bar and placed in a SiC graphite crucible and the metal matrix is formed by melting it and stirring casting metal to add the reinforcement particles. The quantity of B4 C & Al2 O3 combined to form the new material was taken at 5% each. The samples were prepared according to ASTM specifications and eventually tested for tensile, compression, hardness, wear and effect measurements, and the findings were compared with those of pure aluminium Al 7075. The test results showed improved properties of Al MMC, which is more efficient than Al 7075.